Gambaran Sanitasi Sekolah Dasar Inpres Palsatu dan Sekolah Dasar Negeri Palsatu pada Kelurahan Manutapen Kecamatan Alak Kota Kupang - Villya Ariyani Lay; Mustakim Sahdan; Soni Doke (Yayasan Literasi Sains Indonesia, 2024)
School sanitation, including the provision of clean water, toilet facilities, hand washing with soap (CTPS), waste bin management, has a big impact. When school sanitation facilities and infrastructure do not meet health standards, lack of Clean and Healthy Living Behavior, as well as lack of sanitation management schools, has negative impact on student health. The aim of the research to describe the sanitation situation at SDI Palsatu and SDN Palsatu using descriptive research methods. The research was conducted in January-February 2024 with a sample of 30 students and principals from each school. The results of research show that condition of clean water supply facilities at SDI Palsatu and SDN Palsatu meets requirements with percentage of 80% and 100%, the condition of latrines at SDI Palsatu and SDN Palsatu does not meet requirements with percentage of 45.45% and 36.36%, the condition of CTPS at SDI Palsatu and SDN Palsatu do not meet requirements with a percentage of 33%, Conditions of waste disposal facilities at SDI Palsatu and SDN Palsatu o not meet requirements with percentage of 20%, The behavior of using latrines for urinating/defecating at SDI Palsatu and SDN Palsatu does not meet requirements with percentages of 54.44% and 55.55%. CTPS behavior at SDI Palsatu and SDN Palsatu meets requirements with percentage of 82% and 78%. Waste management behavior at SDI Palsatu and SDN Palsatu does not meet requirements with percentage of 33.33% and 26.66%. Sanitation management at SDI Palsatu and SDN Palsatu is good with percentage of 71.42% and 85.71%.